The influence of viscosity of hydrogels on the spreading and migration of cells in 3D bioprinted skin cancer models - Du Plessis, Lissinda H.; Gouws, Chrisna; Nieto, Daniel (Frontiers in Cell and Developmental Biology, 2024)
Various in vitro three-dimensional (3D) tissue culture models of human and diseased skin exist. Nevertheless, there is still room for the development and improvement of 3D bioprinted skin cancer models. The need for reproducible bioprinting methods, cell samples, biomaterial inks, and bioinks is becoming increasingly important. The influence of the viscosity of hydrogels on the spreading and migration of most types of cancer cells is well studied. There are however limited studies on the influence of viscosity on the spreading and migration of cells in 3D bioprinted skin cancer models. In this review, we will outline the importance of studying the various types of skin cancers by using 3D cell culture models. We will provide an overview of the advantages and disadvantages of the various 3D bioprinting technologies. We will emphasize how the viscosity of hydrogels relates to the spreading and migration of cancer cells. Lastly, we will give an overview of the specific studies on cell migration and spreading in 3D bioprinted skin cancer models.